RSPCA and the criminology of social control - Hughes, Gordon (2011)
This paper contributes to a rethinking of animal abuse control and animal welfare protection in criminology, specifically, and in the social sciences more broadly. We do this, first, through a broad mapping of the institutional control complex around animal abuse in contemporary Britain. Second, we focus on the institutional strategies and practices, past and present, of the main agency of animal protection, and the policing thereof, in this society, namely the Royal Society for the Prevention of Cruelty to Animals (RSPCA). In looking back to this charity’s growth since the first decades of the nineteenth century at the time of the birth of modern industrial capitalism and also to its current rationale and practices as a late-modern, corporate organisation, we explore the seeming paradox of a private body taking a lead on the regulation and prosecution of illegalities associated with animal-human relationships. Finally, the ideology and strategy of the RSPCA are explored in the con